Problem prejudycjalnego związania sądu polubownego wyrokami sądów powszechnych i polubownych - Chyla, Łukasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The aim of the article is to present a highly controversial issue whether the legal effects of prejudicial awards of either common court or arbitration court shall be binding for another arbitration tribunal resolving the same dispute between the same parties. This issue is broadly disputable, essentially after the Polish Supreme Court delivered two contrary judgments regarding this matter. Arguably, it remains unclear whether art. 365 of the Polish Code of Civil Procedure is applicable not only to common courts but also to arbitration tribunals. Moreover, because of the preliminary meaning of art. 1184 of the CCP, it is also questionable whether arbitration courts are bound by some provisions of civil procedure, specifically art. 365 of the CCP. The aim of this article is to analyze and address these legal issues as well as to explain why, in my opinion, arbitration tribunals shall eventually be bound by earlier awards — either those delivered by the common courts or arbitration tribunals.
Keywords: prejudicial legal effects; prejudicial awards; arbitration; binding effect of prejudicial awards